(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
The research dealt with the design of the cost accounting system for the transport service and its Role in improving the efficiency of pricing decisions through the application of the cost system based on ABC activities. The main activities were defined and cost guides were to measure the cost of each service and to determine the cost of each service for the purpose of providing management with appropriate information and pricing decisions The problem of research in the lack of adoption by some public companies in the service sector on the cost accounting system to calculate the cost of service as well as the lack of identification of productive activities and service activities and therefore cannot make the appropriate decision to the pricing of its services fairly and rationally. The aim of the research is to design a system of cost accounting based on ABC activities in the service sector to calculate the cost of service for the purpose of providing appropriate information to the administration for the purpose of increasing the effectiveness of pricing decisions for those services. The main findings of the research that the use of cost accounting system helps to identify and measure the cost of transport services correctly and thus the possibility the administration should make a rational and rational decision to price services more fairly and objectively.